Forceful Self‐Help and Private Voice: How Schauer and McAdams Exaggerate a State's Ability to Monopolize Violence and Expression. Issue 1 (28th November 2016) - Ellickson, Robert C.
Abstract : Frederick Schauer's The Force of Law (2015) and Richard McAdams's The Expressive Powers of Law (2015) are noteworthy contributions. However, both authors exaggerate the importance of law, as opposed to other means of social control. Schauer largely omits the role that self‐help measures, ranging from negative gossip to violent self‐defense, play in deterring misconduct. Contrary to Max Weber, the state in practice cannot monopolize the legitimate use of physical force. McAdams valuably analyzes law's potentially expressive effects. He might have devoted more attention, however, to identifying the contexts in which state speech tends to be more salient than private speech, such as a statement by the pope or another esteemed private pundit.